Breast Cancer Textbook for General Practitioners - Veronesi, Umberto (Springer Berlin Heidelberg, 1990)
The "Europe against Cancer" programme has, from its inception, emphasised the key role which general practitioners must play in the actions necessary to achieve its aim of reduc ing the incidence and the mortality from cancer in the European Community. General practitioners, because of their day-to-day direct and continuing contact with patients, playa role not only in primary prevention and education of patients, but also in motivating their patients to accept secondary prevention and screening, some of it carried out by general practitioners themselves. These preventive activities are in addition to their traditional role in the care and management of patients with cancer at home, and increas ingly, their role in active treatment. In view of the importance of the general practitioner in the "Europe against Cancer" pro gramme, the European Commission, with a view to providing general practitioners with up-tO-date useful information, has sponsored the production of this series of publications on organ based cancers, especially written for general practitioners. MICHEL RICHONNIER Coordinator of the" Europe against Cancer" programme, Commission ofthe European Communities, Brussels Preface The present textbook is the second in the series published by the Commission of the Euro pean Communities within the context of the "Europe Against Cancer" Programme. After lung cancer, it was felt that priority should be given to breast cancer, the most frequent neoplastic disease among European women
Keywords: Oncology; Gynecology; Cancer Research; Oncology; Brustkrebs